Radar data monitoring improvement / Anuar Abdul Kader - Abdul Kader, Anuar (1994)
Radar equipment operates by radiating electromagnetic energy and detecting the presence and character of the echo returned from reflecting objects. It is an active device that utilizes its own controlled illumination to detect the target and to probe the target characteristics. It does not depend on the energy radiated by the target itself The radar signal is usually in the form of repetitive train of short pulses, generated by a transmitter and radiated into space by an antenna. A single antenna is used for both transmission and reception. Reflecting objects or targets intercept and reradiate a portion of the radar signal; a small amount returns in the direction of the radar. This signal is processed and the output is used to monitor the condition of the radar system. The purpose of this project is to design the hardware for improving the radar data monitoring system in the primary radar display and data handling system at Subang Airport.